Patient specific lumped parameter modeling of penile erection mechanism relying on reduced penile doppler ultrasound data - Yıldırım, Canberk. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Erectile dysfunction (ED) is a common clinical condition that affects 10-20% of the male population. Penile color Doppler ultrasound (PDUS) is considered as the most objective erection evaluation method, which solely relies on the average blood flow passing through the cavernosal arteries during systole and diastole of the heart. How ever, this method is somewhat invasive and its diagnostic accuracy is inadequate due to the lack of intracavernosal pressure (ICP) measurement, which is the most precise and direct evaluation parameter of erectile function. On the other hand, highly invasive cavernosometry test is the only measurement method for the ICP. Therefore, a pulsatile lumped parameter model of penile circulation system is developed and coupled to the patient-specific bi-ventricular circulation system to predict the erectile function includ ing the penile pressures and volumes of the system quantitatively and noninvasively. The proposed model is validated by the pre-and post-papaverine injection PDUS and ICP data of 4 ED complaint patients. The numerical model provides detailed hemo dynamic information through the employed sensitivity study for both penile erection and bi-ventricular circulation parameters. Moreover, for the diseased patients studied the model predicts the ICP noninvasively with an average error value of 3 mmHg for both pre-and post-injection phases. In addition, penile size change during the phases of erection is simulated with approximately 15% error, according to the clinical penile size measurements. As a result, the developed mathematical model has a potential to be used as an effective non-invasive tool in patient-specific erectile function evaluation, expanding the existing clinical decision parameters significantly.
Keywords: Impotence.; Doppler ultrasonography.